MENYIKAP TABIR KONTRADIKTIF HADITS CARA SUJUD - Simamora, Khairul Fadli (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2025)
AbstractThe pillars of prayer are an important part of the prayer itself and the validity of the prayer depends on it. In the process of prostrating procedures, there are several variations, there are contradictory hadith editions. The author will examine the hadith contained in Sunan Abu Dawud, namely the hadith of putting your hands first and putting your knees first when prostrating. The problem that will be studied is the authenticity of the hadiths regarding putting the hands first or putting the knees first when prostrating and how to respond to differences in the editorials of these hadiths. The phenomenon that occurs in society is not knowing which quality of hadith is superior. Meanwhile, the community's practices are in accordance with those obtained from lessons at an early age or relying on materials when studying at the diniyyah or ibtidaiyyah school as well as the teachings of their parents, known as the taqlid community. In the case of differences in the procedures for prostrating, this causes disagreements resulting in mutual blame. This research will analyze literature regarding the comparative quality of history, relationships and forms of practice of the two hadiths, which is often called library research. With this research, it is concluded that both hadiths are hadiths that can be accepted as hujjah or maqbul, the quality of the hadith on putting hands first is higher because it has the quality of șahih ligairihi, while the hadith about putting knees first has the status of hasan ligairihi. In the science of ulumul hadith, the level of șahih ligairihi hadith is higher than hasan ligairihi hadith. With the existence of these two different hadiths, it brings the path of maslahah or convenience to musholli, not the other way around, let alone reaching the realm of disputes in society.